A chemoreceptor conformational equilibrium controlled by signaling inputs - Mikaila C. Hoffman; Mingshan Li; Gerald L. Hazelbauer; Gabriela S. Schlau-Cohen (Proceedings of the National Academy of Sciences, 2025)
In chemotaxis, motile bacteria recognize external molecules and move toward favorable concentrations. Chemoreceptors form complexes that perform transmembrane signaling, control a histidine kinase, and undergo posttranslational adaptational modifications. Chemoreceptors are thought to function by switching between two signaling states: kinase-off, favored by ligand occupancy, and kinase-on, favored by adaptational modification. Many structural and biochemical features of the two states have been identified, but little is known about the equilibrium between them and the response of that equilibrium to signaling inputs. Using single-molecule Förster resonance energy transfer, we monitored helical separations in the Escherichia coli aspartate chemoreceptor Tar for the two pairs of helices that form the cytoplasmic four-helix coiled coil bundle. Rather than the commonly assumed switch between two conformations in response to signaling inputs, we identified two separations in each helical pair that were present under all conditions but with variation in relative occupancy. Ligand occupancy and adaptational modification were found to differentially impact the conformational equilibria, rather than reversing the same conformational response, as previously thought. Ligand occupancy changed symmetrical packing in the four-helix bundle into rhomboid packing, whereas adaptational modification determined which helical pair was central in the rhombus. Thus, the structural consequence of ligand binding was not stabilization of a specific helical conformation but instead the collective geometry of all helices in the bundle. Such changes in helical geometry may play a role in conformational signaling by other transmembrane receptors.